Optimizing the Role of Mediators in Resolving Workers’ Rights Disputes: Optimalisasi Peran Mediator dalam Menyelesaikan Perselisihan Hak Pekerja - Raqel Elang Pangestu, Muhammad; Putra Maya Padaloka, Rocky; Rambu Rambuni, Arraya (Mendapo: Journal of Administrative Law, 2025)
Industrial relations disputes, particularly rights disputes following termination of employment, frequently arise due to differences in interpretation and implementation of rights and obligations between workers and employers. Mediation is prioritized as a non-litigation dispute resolution mechanism before cases proceed to the Industrial Relations Court. This study aims to analyze the role of mediators at the Tangerang Regency Manpower Office in resolving rights disputes and to identify factors that hinder the effectiveness of the mediation process. This research employs an empirical legal research method with a qualitative approach, using interviews and field observations conducted during an internship program. The findings indicate that mediators have performed their roles in facilitating dialogue, examining documents, and issuing recommendations; however, the effectiveness of mediation is often constrained by the absence of disputing parties, incomplete documentation, differences in legal interpretation, and the non-binding nature of mediation recommendations. The novelty of this study lies in its empirical finding that mediation recommendations at the regional level tend to function merely as administrative formalities, limiting their effectiveness in strengthening the protection of workers’ rights. This study recommends strengthening mediator authority and improving the substantive quality of mediation outcomes to achieve a more effective and equitable industrial dispute resolution mechanism.